2008
DOI: 10.1088/0953-8984/20/11/114112
|View full text |Cite
|
Sign up to set email alerts
|

Liquid carbon density and resistivity

Abstract: As was shown in Gathers et al (1974 Report UCRL-51644 (Lawrence Livermore Laboratory, September 14)), graphite specimens of low initial densities (heated at gas pressure 2-4 kbar) contract to higher density still in the solid state and then continue further expanding up to the melting line. This effect was included in the analysis of our experimental results on the fast heating of graphite specimens in thick-walled capillary tubes. At low pressures (up to 4 kbar) the liquid carbon density γ∼1.2 g cm(-3). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[16] is more tetrahedral than C*, the potential with λ = 26.2 of the family of this study, and produces a very low-density liquid (about half of the density of the crystal) in qualitative agreement with the experiments that indicate that the density of liquid carbon is even lower, about one third of the density of diamond. [79] Most noteworthy in Figure 1 is the lack of density anomaly for both low and high values of tetrahedral parameter λ. The density anomaly, a density maximum followed by a density minimum at lower temperatures, is only observed for the liquids with tetrahedral parameter in the range 20 < λ < 26.4.…”
Section: Densitymentioning
confidence: 92%
“…[16] is more tetrahedral than C*, the potential with λ = 26.2 of the family of this study, and produces a very low-density liquid (about half of the density of the crystal) in qualitative agreement with the experiments that indicate that the density of liquid carbon is even lower, about one third of the density of diamond. [79] Most noteworthy in Figure 1 is the lack of density anomaly for both low and high values of tetrahedral parameter λ. The density anomaly, a density maximum followed by a density minimum at lower temperatures, is only observed for the liquids with tetrahedral parameter in the range 20 < λ < 26.4.…”
Section: Densitymentioning
confidence: 92%
“…Our results on carbon expansion obtained in sapphire capillary tubes (and between sapphire plates) at the melting line are shown in the Table 1 [3,4]. Togaya [5] obtained linear dependence between rising pressure P and diminishing of the imparted energy E M at the finish of melting.…”
Section: Data On the Liquid Carbon Propertiesmentioning
confidence: 60%
“…2) suggest as probable. If we also take into consideration the significant differences between the densities of melted carbon (~1.2 -1.8 mg/cm 3 ) [45] and graphite (2 -2.2 mg/cm 3 ) a local melting process will try to produce a 'local' increase of several tens of percent of the materials' volume inducing significant pressures over graphite solid boundaries. As some studies have shown, the graphite could be significantly compressed (up to 75 % [46]) but with great 'costs' in the crystal structure.…”
Section: Resultsmentioning
confidence: 99%